Covalently-functionalized graphene oxide via introduction of bifunctional phosphorus-containing molecules as an effective flame retardant for polystyrene. Issue 44 (11th July 2018) - Dai, Kang; Sun, Shuai; Xu, Wenbin; Song, Yuan; Deng, Zhenzhen; Qian, Xiaodong
Abstract : A covalently-functionalized graphene oxide with excellent flame retardancy was successfully prepared. Abstract : Covalently-functionalized graphene oxide (FGO) was successfully prepared by grafting a novel phosphorus-containing flame retardant, [2-((6-oxidodibenzo[ c, e ][1, 2]oxaphosphinin-6-yl)methoxy)acryloxyethylchlorophosphate, PACP], to graphene oxide (GO). The resulting FGO demonstrated hydrophobicity and stability in polar solvents such as N, N -dimethylformamide (DMF). The reactive vinyl groups of PACP attached to FGO further copolymerized with styrene to produce polystyrene-FGO (PS-FGO) nanocomposites. PS-FGO samples showed obviously improved fire-resistance, thermal behavior and glass transition temperature in comparison with those of neat PS and PS-GO samples, due to the good dispersion of FGO in PS as well as the strong interfacial bonds between FGO and the matrix. In addition, thermogravimetry-Fourier transform infrared (TG-FTIR) results indicated that the evolution of volatile products from PS decomposition was significantly inhibited by the introduction of FGO. Furthermore, scanning electron microscopy (SEM) and FTIR and Raman spectroscopy were employed to investigate the char residue, elaborating the flame-retardance mechanism.